PENERAPAN PRINSIP HAKIM PASIF DAN AKTIF SERTARELEVANSINYA TERHADAP KONSEP KEBENARAN FORMAL - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2010)
The conception of formal truth in civil procedure is about to become a debate among academicians and practitioners because it is deemed no longer relevant to achieve justice. Modern paradigm begins to consider that this concept should be given similar interpretation with material truth theory adhered by criminal procedure.